Analisis Yuridis Standar Operasional Prosedur Penggunaan Ambulan di Puskesmas Andong Untuk Pelayanan Rujukan Berdasarkan PERMENKES Nomor 71 Tahun 2013 - Darmanto, Darmanto; Santoso, Aris Prio Agus; Rezi, Rezi; Elisanti, Evi (Fakultas Syariah INSURI Ponorogo, 2023)
The aim of this research is to 1) determine the application of standard operational procedures for ambulance referral services at the Andong Community Health Center based on PERMENKES Number 71 of 2013, 2) determine the obstacles to the Community Health Center in providing referral services. Sociological juridical research method with a qualitative approach. The primary data source is text from interviews and was obtained through interviews with informants in the research. Secondary data is data obtained by researchers by studying literature such as journals, articles, books, documents and others. Data collection techniques were carried out by means of interviews, observations and documents. There are several stages in the qualitative descriptive analysis technique, namely data reduction, data presentation, and verification. The results of the research show that the SOP for the use of ambulances in referral services at the Andong Health Center is in accordance with the existing SOP, however the SOP for the use of ambulances in referral services must be further improved so that it is optimally in accordance with PERMENKES Number 17 of 2013. The main objective of the SOP is to provide guidance or guidance on using an ambulance. The obstacle to the Puskesmas in providing referral services is the lack of human resources (drivers) consisting of 1 person with 2 ambulances. Meanwhile, the infrastructure is in accordance with basic ambulance service standards. The conclusion of this research is that the application of standard operational procedures is very effective and efficient in improving ambulance referral services at the Andong Community Health Center and resolving barriers to referral services.